2018
DOI: 10.1111/sipr.12043
|View full text |Cite
|
Sign up to set email alerts
|

Weight Bias and Stigma: Public Health Implications and Structural Solutions

Abstract: Weight bias is a widespread form of prejudice that leads to the stigmatization of individuals who are perceived to have excess weight. Several psychological theories have been used to explain weight bias and to understand its negative impact on the mental and physical health of individuals with overweight and obesity. Top‐down approaches are needed to reduce weight stigma and its adverse health consequences at the population‐level. Potential targets for stigma‐reduction policies include weight‐based discrimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
138
2
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(146 citation statements)
references
References 209 publications
(304 reference statements)
1
138
2
5
Order By: Relevance
“…These programs should be specifically aimed at the PT practitioners [13]. Furthermore, within PT/health care settings, regulations should be enforced [47] in order to create physical environments that are suitable for individuals with obesity. Such environments should include appropriately sized equipment and attire (e.g., beds, wheelchairs, appropriate gowns, etc.…”
Section: Discussionmentioning
confidence: 99%
“…These programs should be specifically aimed at the PT practitioners [13]. Furthermore, within PT/health care settings, regulations should be enforced [47] in order to create physical environments that are suitable for individuals with obesity. Such environments should include appropriately sized equipment and attire (e.g., beds, wheelchairs, appropriate gowns, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial research has demonstrated that weight stigma and discrimination are pervasive, global issues 7,8 . Weight stigma has been documented in multiple societal domains, including the workplace, education, healthcare settings, and within families 9,10 . Stigma has persisted despite the markedly increased prevalence of obesity in recent decades.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…A large body of evidence suggests that people with obesity are highly stigmatized and experience high levels of discrimination (Pearl, ; Roehling, Roehling, & Wagstaff, ; Rudolph, Wells, Weller, & Baltes, ; Vanhove & Gordon,). The more excess weight a person carries, the greater the discrimination experienced (Roehling, Roehling, & Pichler, ).…”
Section: Introductionmentioning
confidence: 99%